Dispersion-Engineered Metasurface Doublet Design for Broadband and Wide-Angle Operation in the Visible Range - Junhyeok Jang; Gun-Yeal Lee; Youngjin Kim; Changhyun Kim; Yoonchan Jeong; Byoungho Lee (IEEE Photonics Journal, 2023)
The development of a metasurface lens, which represents a flat optical element with subwavelength thickness, holds the potential for miniaturizing imaging systems. Nevertheless, the presence of aberrations poses a significant challenge for achieving optimal imaging quality out of it. Moreover, its practical utilization in cameras and wearable devices necessitates simultaneous correction of monochromatic and chromatic aberrations. We here propose a framework to design multi-layered, dispersion-engineered metasurfaces, which is capable of correcting monochromatic and chromatic aberrations in a simultaneous manner. Based on the scheme, we numerically demonstrate a novel metasurface doublet that gives rise to significant improvement in correction of both monochromatic and chromatic aberrations. The designed lens has a field-of-view of 50° and operates in the broadband visible region from 450 to 650 nm.